Design and validation of a new questionnaire with a gender perspective to measure medication adherence for secondary prevention of ischaemic heart disease: study protocol - Leticia Fernandez-Friera; Rauf Nouni-Garcia; Concepcion Carratala-Munuera; Domingo Orozco-Beltran; Adriana Lopez-Pineda; Virtudes Pérez-Jover; Vicente Bertomeu-González; Pablo Martinez Perez; Alberto Cordero; Jose A Quesada; Jose Maria Castellano-Vazquez; Andreu Nolasco; et al. (BMJ Open)
Introduction and objectives Only about 50% of chronic patients in high-income countries adhere to their treatment. There are methods to measure medication adherence but none of them can be considered optimal. This study will aim to design and validate a questionnaire to measure medication adherence in patients with ischaemic heart disease using a direct method as a gold-standard adherence measure and taking into account the gender perspective. Moreover, the profile of low adherence in these patients will be determined.Methods and analysis First study phase consists on the questionnaire design following the next steps: identification of the dimensions, definition of the target population, questionnaire items and order, response coding, questionnaire instructions, content validity by experts and understandability. In the second phase, a cross-sectional study will be performed to end the questionnaire development and validate it. Four hundred and forty patients (50% female) with acute coronary syndrome receiving treatment within the previous 12 months will be included. Patient will answer the initial questionnaire and adherence to aspirin and statin will be measured using a direct method (drug concentration analysis in blood) and other questionnaires. From the set of preselected questionnaire items, those most closely associated with the gold standard measure will be selected using multivariate statistics.Ethics and dissemination All participants gave their written informed consent before participating in the study. The study protocol follows the recommendations of the Declaration of Helsinki and was approved by the ethics committees of the three participating centres. The results of this study will be displayed at national and international conferences and in peer-reviewed scientific journals.